(untitled) (The Chittagong University Journal of Science, 2022)
An understanding of the front propagation in a dynamically unstable state requires a theory that treats the superconducting-normal (SN) interfaces as a free boundary problem. The relevance of an interfacial representation based on dynamics of the superconducting order parameter and vector potential. When magnetic flux diffuses into the normal phases the interfacial dynamics can be determined by the free boundary model. This model involves surface tension for the motion of the interface which has been calculated by the exact solution of TDGL equation [8].This analytical result of the surface tension agrees with that of Osborn and Dorsey [9]. The Chittagong Univ. J. Sci. 43(1): 31-40, 2021